96.7k views
12 votes
Solve the polynomial equation by factoring.
3x^4+11^3-4x^2=0

2 Answers

4 votes

Explanation:


3{x}^(4) + 11 {x}^(3) - 4 {x}^(2) = 0 \\ factor \: {x}^(2) out \: of \: 3 {x}^(4) + 11 {x}^(3) - 4 {x}^(2) \\ \\ {x}^(2) ( 3{x}^(2) + 11x - 4) = 0 \\ {x}^(2) (3x - 1)(x + 4) = 0 \\ {x}^(2) = 0 \\ 3x - 1 = 0 \\ x + 4 = 0 \\


x = 0 \\ x = (1)/(3) \\ x = - 4 \\

The final solution is

x=(0 , 1/3 , -4 )

User Bitsabhi
by
6.4k points
7 votes

Answer:

0

Explanation:

User Nass
by
6.1k points